Mathematical Description and Laboratory Study of Electrophysical Methods of Localization of Geodeformational Changes during the Control of the Railway Roadbed - Bykov, A.; Grecheneva, A.; Kuzichkin, O.; Surzhik, D.; Vasilyev, G.; Yerbayev, Y. (MATHEMATICS. - 2021., 2021)
Currently, the load on railway tracks is increasing due to the increase in freight traffic. Accordingly, more and more serious requirements are being imposed on the reliability of the roadbed, which means that studies of methods for monitoring the integrity of the railway roadbed are relevant. The article provides a mathematical substantiation of the possibility of using seismoelectric and phasemetric methods of geoelectric control of the roadbed of railway tracks in order to identify defects and deformations at an early stage of their occurrence. The methods of laboratory modeling of the natural-technical system "railway track" are considered in order to assess the prospects of using the presented methods. The results of laboratory studies are presented, which have shown their high efficiency in registering a weak useful electrical signal caused by seismoacoustic effects against the background of high-level external industrial and natural interference. In the course of laboratory modeling, it was found that on the amplitude spectra of the output electrical signals of the investigated geological medium in the presence of an elastic harmonic action with a frequency of 70 Hz, the frequency of a harmonic electrical signal with a frequency of 40 Hz is observed. In laboratory modeling, phase images were obtained for the receiving line when simulating the process of sinking the soil base of the railway bed, confirming the presence of a transient process that causes a shift in the initial phase of the signal Delta phi = 40 degrees by ~45 degrees (Delta phi' = 85 degrees), which allows detection of the initial stage of failure formation. В настоящее время увеличивается нагрузка на железнодорожные пути в связи с увеличением грузопотока. Соответственно, к надежности земляного полотна предъявляются все более серьезные требования, а значит, актуальны исследования методов контроля целостности земляного полотна. В статье дано математическое обоснование возможности использования сейсмоэлектрических и фазометрических методов геоэлектрического контроля земляного полотна железнодорожных путей с целью выявления дефектов и деформаций на ранней стадии их возникновения. Рассмотрены методы лабораторного моделирования природно-технической системы «железнодорожный путь» с целью оценки перспективности использования представленных методов. Представлены результаты лабораторных исследований, показавшие их высокую эффективность при регистрации слабого полезного электрического сигнала, вызванного сейсмоакустическими воздействиями, на фоне внешних техногенных и природных помех высокого уровня. В ходе лабораторного моделирования установлено, что на амплитудных спектрах выходных электрических сигналов исследуемой геологической среды при наличии упругого гармонического воздействия частотой 70 Гц частота гармонического электрического сигнала частотой 40 Гц. При лабораторном моделировании были получены фазовые изображения для приемной линии при моделировании процесса просадки грунтового основания железнодорожного полотна, подтверждающие наличие переходного процесса, вызывающего сдвиг начальной фазы сигнала Delta phi = 40 градусов на ~45 градусов (Delta phi' = 85 градусов), что позволяет выявить начальную стадию образования разрушения
Keywords: импакт-фактор 2021; кларивате аналитикс; web of science; научный журнал; периодическое издание; зарубежное издание; дальнее зарубежье; зарубежные авторы; энергетика; железнодорожный транспорт; электрический сигнал; скопус